Farm animal behavior : characteristics for assessment of health & welfare - Ekesbo, Ingvar (Wallingford, Oxfordshire ; Cambridge, Massachusetts : CABI, 2011)
Animal behaviour is the basis for ascertaining their welfare. This undergraduate-level textbook is organised into three sections covering all major farm animals of the world, both mainstream and specialist: large farm animal species (horses, cattle, swine, sheep and goats), poultry and farmed birds and non-domesticated animals such as deer
1. Domesticated mammals -- 2. Domesticated birds -- 3. Non-domesticated farmed animals
Includes bibliographical references (p. 195-221) and index
Keywords: Animal health; Animal welfare; Livestock -- Behavior